In vitro hypoglycemic activity of polysaccharides digested from Nostoc sphaericum Vaucher ex Bornet & Flahault (cushuro) - Inocente Camones, Miguel Angel (2019)
Objective: To evaluate the inhibitory potential of the α-amylase and α-glucosidase enzymes, as well as the inhibition of glucose diffusion, using polysaccharides isolated from Nostoc sphaericum Vaucher ex Bornet & Flahault and treated by in vitro simulated gastrointestinal digestion. Materials and methods: The polysaccharides obtained from the microalga were purified and treated through in vitro gastrointestinal digestibility in order to simulate digestion. The hypoglycemic activity was evaluated by methods such as the inhibition of α-glucosidase and α-amylase, and glucose diffusion of the digested polysaccharides, and compared with the medication acarbose. Results: The results showed that the concentration of 50 mg/mL of digested polysaccharides decreases by 85.26 % the spread of in vitro glucose. The inhibitory concentration (IC50) of the α-glucosidase enzyme was 314.23 ± 4.87 mg/mL and that of the α-amylase enzyme was 113.59 ± 3.10 mg/mL. Conclusions: Nostoc sphaericum polysaccharides treated by in vitro gastrointestinal digestion showed the ability to inhibit the α-amylase and α-glucosidase enzymes, and glucose diffusion. Therefore, this species would be considered promising for a possible adjuvant treatment of type 2 diabetes.